Pengaruh Pemberian Dosis Pupuk Za terhadap Pertumbuhan Awal Tanaman Tebu (Saccharum officinarum) Varietas PS 80-148 - Supandji, Supandji; Muharram, Muhammad; Agusty, Virgian Galuh; Yuliana, Luluk (Agrotrop : Journal on Agriculture Science, 2024)
The Effect of Dosage of Za Fertilizer on The Initial Growth of Sugarcane (Saccharum officinarum) Variety PS 80-148. Sugarcane is one of the important ingredients in the process of making sugar in Indonesia. The initial growth of sugarcane plants is the beginning and subsequent development, therefore by providing fertilizers that match the needs of the plants can increase the productivity of sugarcane plants. In sugarcane cultivation, ZA is the fertilizer that must be applied because it does not have an impact on reducing sugar levels (yield), in contrast to just giving urea fertilizer. The purpose of this study was to determine the effect of ZA dosing on the early growth of sugarcane plants. This research was carried out in the field using a randomized block design (RBD) consisting of one factor repeated four times. ZA fertilizer dose treatment factor: B0 = Without giving ZA, B1 = Giving a dose of 150 Kg ZA / Ha, B2 = Giving a dose of 300 Kg ZA / Ha, B3 = Giving a dose of 450 Kg ZA / Ha, B4 = Giving a dose of 600 Kg ZA / Ha, and B5 = Giving a dose of 750 Kg ZA / Ha. ZA fertilizer dose of 600 kg / ha showed the best treatment for the percentage of shoot growth, which was 76.25%, plant height was 53.00 cm, number of leaves was 14.12 strands. Then the dose of ZA fertilizer 600 kg / ha showed the best treatment for the number of tillers, namely 7.43 stems, stem diameter of 15.82 cm.